Ancient islands acted as refugia and pumps for conifer diversity. (8th March 2016) - Condamine, Fabien L.; Leslie, Andrew B.; Antonelli, Alexandre
Abstract: Island species are thought to be extinction‐prone because of small population sizes, restricted geographical distribution and limited dispersal ability. However, the topographical and environmental heterogeneity, geographical isolation and stability of islands over long timescales could create refugia for taxa whose source area is threatened by environmental changes. We address this possibility by inferring the evolution of the New Caledonia (NC) and New Zealand (NZ) conifer diversity, which represents over 10% of the world's diversity for this group. We estimate speciation and extinction rates in relation to the presence/absence on these islands, and dispersal rates between the islands and surrounding areas. We also test the Eocene submersion of NC and the Oligocene drowning of NZ by comparing the fit of biogeographical scenarios using ancestral area estimations. We find that extinction rates were significantly lower for island species, and dispersal "out of islands" was higher. A model including a diversification shift when NC emerged better explains the diversification dynamics. Biogeographical analyses corroborate that conifers experienced high continental extinctions, but survived on islands. NC and NZ have thus contributed to the world's conifer diversity as "island refugia", by maintaining early‐diverging lineages from continents during environmental changes on continents. These ancient islands also acted as "species pumps", providing species into adjacent areas. Our study highlights the important but neglected role of islands in promoting the evolution and conservation of biodiversity.